2020
DOI: 10.1523/jneurosci.1499-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Mechanisms Governing Sex Differences in Hyperalgesic Priming Involve Prolactin Receptor Sensory Neuron Signaling

Abstract: Neuroendocrine mechanisms governing sex-differences in chronic pain involve prolactin receptor sensory neuron signaling Abbreviated Title: Prolactin promotes chronic pain in females

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 82 publications
2
46
1
1
Order By: Relevance
“…Our findings support the conclusion that CGRP promotes mechanical sensitization in the DRG/spinal cord system, but primarily in female rodents. This adds to a growing body of evidence identifying signaling pathways that promote pain specifically in female animals in numerous models of chronic pain (Patil et al, 2013; Sorge et al, 2015; Avona et al, 2019; Patil et al, 2019b; Patil et al, 2019a; Paige et al, 2020; Avona et al, 2021). We found that CGRP, acting both in the periphery and CNS regulates early pain signaling in female mice and rats but that more persistent effects, such as those involved in the maintenance of hyperalgesic priming, require CNS CGRP signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings support the conclusion that CGRP promotes mechanical sensitization in the DRG/spinal cord system, but primarily in female rodents. This adds to a growing body of evidence identifying signaling pathways that promote pain specifically in female animals in numerous models of chronic pain (Patil et al, 2013; Sorge et al, 2015; Avona et al, 2019; Patil et al, 2019b; Patil et al, 2019a; Paige et al, 2020; Avona et al, 2021). We found that CGRP, acting both in the periphery and CNS regulates early pain signaling in female mice and rats but that more persistent effects, such as those involved in the maintenance of hyperalgesic priming, require CNS CGRP signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In females, depletion of microglia does not reverse nerve injury-induced hypersensitivity and it appears that Tcells may play a critical role in promoting chronic pain (Sorge et al, 2015), although there is also evidence that T-cells promote pain resolution in both sexes (Krukowski et al, 2016;Laumet et al, 2019). Another female-specific pain promoting mechanism is prolactin signaling, which sensitizes female nociceptors through a direct action on the prolactin receptor (Patil et al, 2013;Patil et al, 2019b;Paige et al, 2020). Two mechanisms could underlie this sex difference in responses to prolactin, a sexually dimorphic expression pattern for the prolactin receptor in subtypes of dorsal root ganglia (DRG) neurons (Patil et al, 2019a), and/or a female-specific translation of the prolactin receptor at central and peripheral terminals of nociceptors (Patil et al, 2019b;Paige et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these animals, higher grimace scores were also recorded. In female mice, already sensitized, for example, by opioids [ 39 ] or the inflammatory agent IL-6 [ 16 ], even lower doses of prolactin could elicit a profound pain response. In search for identification of interaction between sex hormones and prolactin, behavioral tests have also shown that administration of prolactin can induce acute nociception in intact females but not in ovariectomized rats [ 38 ].…”
Section: Prolactin and Migraine: Basic Researchmentioning
confidence: 99%
“…Interestingly, hypersensitivity levels of stressed animals that received bromocriptine returned to baseline faster. Studies have also found that knockout of the prolactin receptor from Nav1.8-expressing nociceptors did not affect males but reduced the priming response to nitric oxide donors after stress in knockout females [ 8 , 16 , 78 ]. Recent data in mice have indicated that different stressors, such as surgery and inflammation, could elevate prolactin levels [ 77 , 79 ] predominantly in females.…”
Section: Prolactin and Migraine: Basic Researchmentioning
confidence: 99%